Kepastian Hukum Pendaftaran Persekutuan Komanditer Pada Sistem Administrasi Badan Usaha - Sudarsa, Dentria Cahya; Parsa, I Wayan (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 5 No 3 (2020), 2020)
The writing of this article is based on the issuance of new regulations regarding the establishment and registration of limited partnership / CV in the business administration system (SABU) in accordance with the provisions of Article 5 paragraph (1) Regulation of the Minister of Law and Human Rights Number 17 of 2018 concerning Registration of Limited Partnerships, Firms, and the Civil Union which previously was only regulated in the Trade Law Book. Type of research used in this article is normative legal research. The purpose of this article is to determine the mechanism and legal certainty in the registration of the Limited Partnership after the enactment of business administration system. The results of the research and writing of this article are that there is an overlap in the registration mechanism for the Limited Partnership based on these two rules, it can be concluded that due to the provisions in KUHD and Minister Regulation No. 17 of 2018 both are still valid, the principle of legal preference can be used, namely lex specialis derogat legi lex generalis, means that a more specific law can override a more general law. The advice that can be given is to conduct a study of the enactment of the Minister Regulation whether to follow or not the provisions in the Trade Law Books due to avoid conflicting norms in the registration of a limited partnership.